2012
DOI: 10.1589/jpts.24.833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hippotherapy on the Sitting Balance of Children with Cerebral Palsy: a Randomized Control Trial

Abstract: Abstract. [Purpose] This study aimed to verify the effect of hippotherapy on the sitting balance of children with severe cerebral palsy (CP) by comparing hippotherapy, physical therapy, and a control. [Subjects] In this study, 45 children with CP were randomly divided into the hippotherapy group (HTG, n = 15), physical therapy group (PTG, n = 15), and control group (CON, n = 15).[Methods] Two expert physical therapists provided the HTG and PTG with traditional physical therapy comprising strengthening and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 16 publications
1
26
0
5
Order By: Relevance
“…To assess the ability to shift body weight, they used a mat which measured the pressure exerted while sitting. Data analysis revealed that patients with cerebral palsy achiev ed greater improvements in their sitting balance with classic exercises supplemented by hip potherapy than with physiotherapy alone [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the ability to shift body weight, they used a mat which measured the pressure exerted while sitting. Data analysis revealed that patients with cerebral palsy achiev ed greater improvements in their sitting balance with classic exercises supplemented by hip potherapy than with physiotherapy alone [21].…”
Section: Discussionmentioning
confidence: 99%
“…sie dze nia, niż sa ma fi zjo te ra pia [21]. Prze pro wa dzo ne przez nas ba da nie po sia da ło pewne ogra ni cze nia.…”
unclassified
“…Even though the effect of CP on postural stability has been previously studied and documented, one can easily see that studies usually do not have pure hemiplegic CP groups 5 , 6 , 7 ) . Most of the rehabilitation studies have involved children with diplegic CP, and the effectiveness of interventions in these children 8 , 9 ) . Patients with hemiplegic CP are usually children who have higher levels of gross motor function 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados mostraron una mejora en el equilibrio sentado tras el programa de hipoterapia, pero dicha mejoría no se mantuvo tras las 12 semanas desde la intervención lo que nos indica que si queremos que la mejoría se mantenga es necesario mantener el programa de hipoterapia de forma continuada. Kang et al (2012) comprobaron los efectos de la hipoterapia sobre el equilibrio sentado en 45 niños con parálisis cerebral. Para ello dividieron de forma randomizada a los niños en tres grupos, un grupo control (n=15) que no recibiría ningún tipo de tratamiento, un grupo que solo realizaría hipoterapia (n=15) y otro grupo que solo realizaría ejercicios de fortalecimiento y estiramiento por parte de fisioterapeutas (n=15), ambos grupos en sesiones semanales de 30 minutos durante ocho semanas.…”
Section: Resultsunclassified